2017
DOI: 10.1007/s11854-017-0031-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-real zeros of derivatives of meromorphic functions

Abstract: A number of results are proved concerning non-real zeros of derivatives of real and strictly non-real meromorphic functions in the plane. MSC 2000: 30D35.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Furthermore, Theorem 1.2 and [24] together show that there are no functions f satisfying the hypotheses of Conjecture 1.1 such that either of the following holds: f has infinite order and the zeros or poles of f have finite exponent of convergence; f has finite order and infinitely many poles but finitely many zeros. The conjecture was also proved in [28,Theorem 1.4] for real transcendental meromorphic functions in the plane which map the open upper half-plane H into itself. All zeros and poles of such functions are automatically real and simple and interlaced [29]: that is, between any two consecutive poles of f there is a zero, and between consecutive zeros of f lies a pole (this follows from a consideration of residues for f and 1/f ).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Furthermore, Theorem 1.2 and [24] together show that there are no functions f satisfying the hypotheses of Conjecture 1.1 such that either of the following holds: f has infinite order and the zeros or poles of f have finite exponent of convergence; f has finite order and infinitely many poles but finitely many zeros. The conjecture was also proved in [28,Theorem 1.4] for real transcendental meromorphic functions in the plane which map the open upper half-plane H into itself. All zeros and poles of such functions are automatically real and simple and interlaced [29]: that is, between any two consecutive poles of f there is a zero, and between consecutive zeros of f lies a pole (this follows from a consideration of residues for f and 1/f ).…”
mentioning
confidence: 86%
“…Theorem 1.7 will be deduced from [28,Theorem 1.4] and the following result involving real meromorphic functions with real zeros and poles such that, with finitely many exceptions, all poles are simple and adjacent poles are separated by at least one zero.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many theorems about the zeros of derivatives of meromorphic functions, since the zeros of derivatives of meromorphic functions play an important role in the study of value distributions of meromorphic functions. The recent research about derivatives of meromorphic functions can be found from [8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%